2018
DOI: 10.18553/jmcp.2018.24.9.896
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Medication Therapy Management Delivery: Implications for Health Care Policy

Abstract: This research and a portion of Snyder's salary were supported by grant number K08HS022119 from the Agency for Healthcare Research and Quality. The content is solely the responsibility of the authors and does not necessarily represent the official views of the Agency for Healthcare Research and Quality. Snyder reports consulting fees from Westat for an evaluation of the CMS Enhanced MTM program. The other authors have nothing to disclose. Portions of this research have been presented as abstracts at the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…9 Moreover, as authors have noted previously, outcomes from MTM services have been mixed. 10 Since the enactment of the Act, a plethora of studies have found that MTM services effectively reduce potentially inappropriate medication use and medication nonadherence. However, a systematic review conducted in the last decade demonstrates substantial variation in performance across PDPs and PDPs have not proven that their MTM services improve patient outcomes or reduce health care expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, as authors have noted previously, outcomes from MTM services have been mixed. 10 Since the enactment of the Act, a plethora of studies have found that MTM services effectively reduce potentially inappropriate medication use and medication nonadherence. However, a systematic review conducted in the last decade demonstrates substantial variation in performance across PDPs and PDPs have not proven that their MTM services improve patient outcomes or reduce health care expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…These findings echo a recent study examining MTM delivery through application of the CCM. That study found that referrals to community resources during MTM delivery was limited, partly due to a lack of pharmacist familiarity with available resources, and that follow‐up MTM consultations were less common …”
Section: Discussionmentioning
confidence: 97%
“…14 found that referrals to community resources during MTM delivery was limited, partly due to a lack of pharmacist familiarity with available resources, and that follow-up MTM consultations were less common. 10 As pharmacist roles have expanded into direct patient care services, optimizing the utilization of pharmacy technicians and other support staff has been a commonly cited consideration. 16 referrals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations